Immunomodulatory potential of secretome from cartilage cells and mesenchymal stromal cells in an arthritic context: From predictive fiction toward reality - Colombini, Alessandra; Libonati, Francesca; Lopa, Silvia; Ragni, Enrico; De Luca, Paola; Zagra, Luigi; Sinigaglia, Federico; Moretti, Matteo; de Girolamo, Laura (Frontiers in Medicine, 2022)
The purpose of the present study is to predict by bioinformatics the activity of the EV-embedded miRNAs secreted by cartilage cells (CCs), adipose- (ASCs) and bone marrow-derived (BMSCs) stem cells and verify their immunomodulatory potential supporting our bioinformatics findings to optimize the autologous cell-based therapeutic strategies for OA management. Cells were isolated from surgical waste tissues of 3 patients who underwent total hip replacement, expanded and the extracellular vesicles (EVs) were collected. The expression of EV-embedded micro RNA (miRNA) was evaluated with the QuantStudio™ 12 K Flex OpenArray® platform. Mientournet and Ingenuity Pathway Analysis (IPA) were used for validated target prediction analysis and to identify miRNAs involved in OA and inflammation. Cells shared the expression of 325 miRNAs embedded in EVs and differed for the expression of a small number of them. Mienturnet revealed no results for miRNAs selectively expressed by ASCs, whereas miRNA expressed by CCs and BMSCs were putatively involved in the modulation of cell cycle, senescence, apoptosis, Wnt, TGFβ, VEGF, Notch, Hippo, TNFα, IL-1β, IGF-1, RUNX2 and endochondral ossification pathways. Cartilage homeostasis, macrophages and T cells activity and inflammatory mediators were identified by IPA as targets of the miRNAs found in all the cell populations. Co-culture tests on macrophages and T cells confirmed the immuno-modulatory ability of CCs, ASCs and BMSCs. The study findings support the rationale behind the use of cell-based therapy for the treatment of OA.